Вдосконалення правового регулювання припинення суб’єктивних прав на земельні ділянки внаслідок їх викупу для суспільних потреб - Кирєєва, І. В.; Kyrieieva, I. V.; ORCID: http://orcid.org/0000-0001-5447-4314 (Вісник Харківського національного університету внутрішніх справ. - 2016. - № 2 (73). - С. 170-175, 2016)
Виконано аналіз окремих елементів механізму примусового викупу земельних ділянок для суспільних потреб. Запропоновано доповнити перелік суспільних потреб, для задоволення яких можливий викуп земельних ділянок, необхідністю виконання державою своїх міжнародних зобов’язань. Акцентовано увагу на необхідності внесення змін до законодавства – зобов’язати власника земельної ділянки, який отримав належним чином оформлене повідомлення про викуп земельної ділянки, повідомити орендаря про викуп відповідної орендованої земельної ділянки.

The author has accomplished the analysis of some elements of the mechanism of compulsory redemption of lands for public needs in order to identify the gaps in the field of legal regulation of the mechanism of suspension of land rights as a result of redemption for public needs and finding their solutions. Based on the analysis of scientific literature it is concluded that nowadays the studied issues of terminating relations of the lease of a land as a result of the redemption of the leased land from the owner to meet public needs are not sufficiently developed and can be improved. The author stressed on the objective nature of the forced termination of the subjective land right as a result of its redemption for public needs regarding the legality of landowner’s conduct. The state authorities or local self-governments only certify appropriate public need in a particular land by their power decisions. The author of the article has revealed the presence of gaps among the range of public needs, to meet which it is possible the land redemption. It is offered to add this range with the need to implement international obligations by the state. Based on the analysis of current legislation it is concluded about the lack of legal provision of the procedure to inform tenants of land about redemption of lands for public needs. Special attention is paid on the need to amend the legislation by the obligations of the owner of a land, who received properly executed notice of redemption of the land, to notify the tenant about the redemption of the related leased land.

Выполнен анализ отдельных элементов механизма принудительного вы- купа земельных участков для общественных потребностей. Предложено дополнить перечень общественных потребностей, для удовлетворения которых возможен выкуп земельных участков, необходимостью выполнения государством своих международных обязательств. Акцентировано внимание на необходимости внесения изменений в законодательство – обязать владельца земельного участка, получившего должным образом оформленное сообщение о выкупе земельного участка, сообщить арендатору о выкупе соответствующего арендованного земельного участка.
Improvement of legal regulation of terminating subjective rights on lands as a result of their redemption for public needs
Усовершенствование правового регулирования прекращения субъективных прав на земельные участки в результате их выкупа для общественных потребностей
Кирєєва І. В. Вдосконалення правового регулювання припинення суб’єктивних прав на земельні ділянки внаслідок їх викупу для суспільних потреб / І. В. Кирєєва // Вісник Харківського національного університету внутрішніх справ. - 2016. - № 2. - С. 170-175.
Кирєєва І. В. "Вдосконалення правового регулювання припинення суб’єктивних прав на земельні ділянки внаслідок їх викупу для суспільних потреб." Вісник Харківського національного університету внутрішніх справ 2 (2016): 170-175.
Kyryeyeva, I.V. (2016), “Improvement of legal regulation of terminating subjective rights on lands as a result of their redemption for public needs” [Vdoskonalennia pravovoho rehuliuvannia prypynennia subiektyvnykh prav na zemelni dilianky vnaslidok yikh vykupu dlia suspilnykh potreb], Visnyk Kharkivskoho Natsionalnoho Universytetu Vnutrishnikh Sprav, No. 2, pp. 170-175.
Keywords: Земельне право. Аграрне право. Land Law. Agrarian Law. Земельное право. Аграрное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; право власності на землю; право землекористування; припинення прав на землю; суспільні потреби у земельній ділянці; відчуження земельних ділянок; порядок припинення прав на землю; land ownership; land use rights; termination of land rights; public needs in land; land alienation; procedure of terminating land rights; право собственности на землю; право землепользования; прекращение прав на землю; общественные потребности в земельном участке; отчуждение земельных участков; порядок прекращения прав на землю